Interannual Modulation of Kuroshio in the East China Sea Over the Past Three Decades - Jo, SeongHyun; Moon, Jae-Hong; Kim, Taekyun; Song, Yuhe Tony; Cha, Hyeonsoo (Frontiers in Marine Science, 2022)
The Kuroshio flowing along the continental shelf break of the East China Sea (ECS) plays an important role in altering regional ocean and climate circumstances. Therefore, changes in Kuroshio intensity have been paid attention in recent years, but it is still a challenge. Previous studies have suggested mesoscale eddies that approach close to the east of Taiwan as a dominant factor modulating interannual Kuroshio intensity in the ECS. However, an extended record of altimetry-based data reveals that the interannual Kuroshio intensity no longer has strong relationship with eddy activities in the Subtropical counter current (STCC) region since early 2000s. Based on observational analyses over the past three decades, we found that the Kuroshio intensity in the ECS can be determined by a combination of two dominant modes: one is the mesoscale eddy activities in the STCC region and the other is low-frequency planetary waves traveling westward across the Pacific basin. The eddy activities have consistently fluctuated over the three decades, but low-frequency waves have become strengthened since early 2000s, thereby modulating the interannual variability of Kuroshio intensity. This study may have implications for decadal prediction of Kuroshio intensity, which may be linked to decadal shift in Pacific climate.